Study on mechanical behavior and damage process of concrete with initial damage under eccentric load - Ge Lina (Nature Portfolio, 2021)
Abstract In order to analyze the influence of eccentric load on mechanical properties and damage process of concrete with initial damage, the eccentric load compression tests of concrete under different confining pressures were carried out with the help of PFC particle flow program. The results show that: the eccentric load does not change the relationship between peak stress, crack initiation stress and confining pressure of concrete under uniform load, but decrease the value of them. The peak stress increasing coefficient under uniform load is higher than that under eccentric load, and the peak stress increasing coefficient increases in a linear function with the confining pressure, and the increasing rate is approximately the same. Under uniaxial compression of eccentric load, a type I shear crack approximately parallel to the loading direction is formed, while under biaxial compression, a bending type shear crack with the lower tip of the initial crack as the inflection point is formed. The number of microcracks in concrete under uniform load and eccentric load can be divided into three stages: the calm period at the initial loading stage, the pre-peak expansion period from crack initiation point to peak point, and the rapid increase period after the peak.